“Kepedulian terhadap Sahabat” untuk Meningkatkan Perilaku Prososial Saksi Bullying di Tingkat Sekolah Menengah Pertama - Reni Apriliawati; Esti Hayu Purnamaningsih (Faculty of Psychology, Universitas Gadjah Mada, 2017)
This study aimed to test the effect of the training module “Kepedulian terhadap sahabat” in improving the prosocial behavior of peer bystanders in middle school. This research used the quasi-experiment method with the untreated control group design with dependent pretest and posttest samples which separated subjects into two groups, experimental group and control group (N: 48). The subjects were bullying bystanders grade 7-8 middle school students. The instrument used in this research were knowledge test as a manipulation check, prosocial scale, and a module of “Kepedulian terhadap Sahabat”. A t-test was used to analyze the difference between the experimental group and the control group. The result shows that “Kepedulian terhadap Sahabat” has an effect on bystanders' prosocial behavior (z=-3.799, p=0.01) on middle school students.